Virus and helper component interactions favour the transmission of recombinant potato virus Y strains. (23rd June 2021) - Mondal, Shaonpius; Wintermantel, William M.; Gray, Stewart M.
Abstract : In recent years, several recombinant strains of potato virus Y, notably PVY NTN and PVY N:O have displaced the ordinary strain, PVY O, and emerged as the predominant strains affecting the USA potato crop. Previously we reported that recombinant strains were transmitted more efficiently than PVY O when they were acquired sequentially, regardless of acquisition order. In another recent study, we showed that PVY NTN binds preferentially to the aphid stylet over PVY O when aphids feed on a mixture of PVY O and PVY NTN . To understand the mechanism of this transmission bias as well as preferential virus binding, we separated virus and active helper component proteins (HC), mixed them in homologous and heterologous combinations, and then fed them to aphids using Parafilm sachets. Mixtures of PVY O HC with either PVY N:O or PVY NTN resulted in efficient transmission. PVY N:O HC also facilitated the transmission of PVY O and PVY NTN, albeit with reduced efficiency. PVY NTN HC failed to facilitate transmission of either PVY O or PVY N:O . When PVY O HC or PVY N:O HC was mixed with equal amounts of the two viruses, both viruses in all combinations were transmitted at high efficiencies. In contrast, no transmission occurred when combinations of viruses were mixed with PVY NTN HC. Further study evaluated transmission using serial dilutions of purified virus mixed with HCs. While PVY NTN HC only facilitated the transmission of the homologous virus, the HCs of PVY O and PVY N:O facilitated the transmission of all strains tested. This phenomenon has likely contributed to the increase in the recombinant strains affecting the USA potato crop.